2011
DOI: 10.1007/s13197-011-0240-4
|View full text |Cite
|
Sign up to set email alerts
|

Detection, partial purification and characterization of bacteriocin produced by Lactobacillus brevis FPTLB3 isolated from freshwater fish

Abstract: Lactobacillus brevis FPTLB3 was isolated from freshwater fish, capable of producing bacteriocin that had broad spectrum of inhibition (3200 AU/ml) against Escherichia coli MTCC 1563, Enterococcus faecalis MTCC 2729, Lactobacillus casei MTCC 1423, Lactobacillus sakei ATCC 15521 and Staphylococcus aureus ATCC 25923. The antimicrobial activity of crude supernatant fluid was stable after heating at 121°C for 60 min and declined thereafter. Stability of antimicrobial activity was observed at pH range of 2.0 to 8.0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 26 publications
2
24
3
Order By: Relevance
“…There have been other reports of possible, cell-associated bacteriocins (Banerjee et al, 2013; Barbour and Philip, 2014; Burmølle et al, 2006; Daba et al, 1994; Dang and Lovell, 2016; Tahara and Kanatani, 1997; Yang et al, 1992), but these prior cases are unlikely to represent contact-dependent killing systems. In most of these cases, significant killing activity was also found in cell-free supernatants and the bacteriocins were typically easily detected in supernatants, suggesting they are primarily secreted into the environment and not exclusively cell-associated as with CdzC and CdzD.…”
Section: Discussionmentioning
confidence: 99%
“…There have been other reports of possible, cell-associated bacteriocins (Banerjee et al, 2013; Barbour and Philip, 2014; Burmølle et al, 2006; Daba et al, 1994; Dang and Lovell, 2016; Tahara and Kanatani, 1997; Yang et al, 1992), but these prior cases are unlikely to represent contact-dependent killing systems. In most of these cases, significant killing activity was also found in cell-free supernatants and the bacteriocins were typically easily detected in supernatants, suggesting they are primarily secreted into the environment and not exclusively cell-associated as with CdzC and CdzD.…”
Section: Discussionmentioning
confidence: 99%
“…Because the technique is semi-quantitative analysis, the population density of saba-narezushi should be determined by quantitative technique such as real-time PCR. Lactobacillus brevis FPTLB3 isolated from freshwater fish produced bacteriocin that inhibited Escherichia coli, Enterococcus faecalis, L. sakei and Staphylococcus aureus (Banerjee et al 2011). The isolate can potentially be used for biopreservation of the food.…”
Section: Resultsmentioning
confidence: 99%
“…The Spotnape pony fish and Sturgeon fish are the potent fish species containing microbiota, which are able to produce BLIS and can prevent the bacterial disease such as Vibrio septicaemia, haemorrhagic septicaemia & bacterial gill diseases (Table ) in aquaculture. There are many researchers reported that the bacteriocins producing bacteria isolated from the freshwater fish possess antagonistic activity against common most fish pathogen A. hydrophila (Vijayabaskar & Somasundaram ; Giri, Sukumaran, Sen, Vinumonia, Banu & Jena ; Banerjee, Dora & Chowdhury ), but the mechanism behind the same is still unknown. Further extensive study is required to obtain more scientific understanding and knowledge to prevent diseases in aquaculture, which ultimately avoiding the loss and spoilage during production of aquaculture product.…”
Section: Bacteriocins Isolated From Fish Microbiotamentioning
confidence: 99%